Climate risks and damage abatement effects of pesticides: Evidence based on four-wave panel data in Nigeria - Takeshima, Hiroyuki; Edeh, Hyacinth O.; Lawal, Akeem; Oniybe, Johnson E.; Daudu, Christogonus K.; Andam, Kwaw S. (International Food Policy Research Institute, 2023)
Managing biotic stress, such as pests, diseases, and weeds, remain critical in enhancing the productivity of agrifood systems in developing countries, including Nigeria. The public sector continues to seek solutions for efficient and effective measures for addressing these biotic stresses, ranging from varietal technologies, improved crop husbandry, and the application of agrochemicals. The field-level evidence remains scarce regarding the effectiveness of these measures in developing countries like Nigeria. Furthermore, increasing climate uncertainty poses further challenges in identifying effective measures. This study assesses the damage abatement effects of agrochemicals in Nigeria and how these effects are affected by weather shocks. We extend the standard damage abatement framework to 4 waves of farm panel data to minimize the potential bias due to the endogeneity in agrochemical use decisions. Our results indicate that weather shocks have significant effects. In particular, rising nighttime minimum temperatures above 20 ℃ have significantly increased damage abatement effects of pesticides in Nigeria. This is possibly because of increased pest activities induced by the warmer nighttime temperatures, which, in the absence of pesticide uses, would cause more significant damage to crops. These results hold for all crops combined, as well as individual crops, including cowpea and maize, for which Nigeria has intensified its effort in pest control through both agrochemicals and Bt varieties in recent years.